Lipophosphoglycan is not required for infection of macrophages or mice by Leishmania mexicana - Ilg, Thomas (Oxford University Press, 2000)
Cell surface lipophosphoglycan (LPG) is commonly regarded as a multifunctional Leishmania virulence factor required for survival and development of these parasites in mammals. In this study, the LPG biosynthesis gene lpg1 was deleted in Leishmania mexicana by targeted gene replacement. The resulting mutants are deficient in LPG synthesis but still display on their surface and secrete phosphoglycan-modified molecules, most likely in the form of proteophosphoglycans, whose expression appears to be up-regulated. LPG-deficient L.mexicana promastigotes show no significant differences to LPG-expressing parasites with respect to attachment to, uptake into and multiplication inside macrophages. Moreover, in Balb/c and C57/BL6 mice, LPG-deficient L.mexicana clones are at least as virulent as the parental wild-type strain and lead to lethal disseminated disease. The results demonstrate that at least L.mexicana does not require LPG for experimental infections of macrophages or mice. Leishmania mexicana LPG is therefore not a virulence factor in the mammalian host.